Effect of heat stress on superovulatory response and biochemical parameters in superovulated Dorper sheep in a semi-arid tropical environment (Research, Society and Development, 2021)
The aim of this study evaluated the influence of thermal stress on the superovulatory response and on the biochemical profile of superpervulated Dorper ewes in a semi-arid tropical environment. 13 Dorper sheep were used, which were submitted to estrus synchronization and superovulatory treatment, in two different periods [thermoneutral (TN) and thermal stress (ET)]. The sheep were inseminated by laparoscopy using frozen semen 42-43 hours after removal of the intravaginal device. Five days after artificial insemination, laparotomy was performed to assess the ovarian response and uterine lavage. Blood was collected to assess variations in serum concentrations of glucose, fructosamine, triglycerides, β-hydroxybutyrate (BHB), creatinine, urea, total protein, albumin, AST / TGO, GGT, Alkaline Phosphatase, Calcium, Phosphate and Magnesium. The thermoneutral (TN) and thermal stress (ET) periods had average temperatures of 22.01 ° C and 27.61 ° C, respectively, with a relative humidity of 31.9%. There is no difference in ovulatory response and recovery of structures between the TN and ET periods. Concentrations of serum metabolites varied between thermal periods and between assessment times. In conclusion, the thermal period does not affect the efficiency of the superovulation protocol in Dorper ewes reared in a semi-arid tropical environment, but causes changes in serum metabolites.